MODELING AND VIBRATION RESPONSE ANALYSIS OF PELLET MACHINE GRINDER AND GEARBOX - Lostari, Aini; Susastro, Susastro; Machfuroh, Talifatim (Universitas Muhammadiyah Jakarta, 2020)
Pellet machine is a machine used to print feed in the form of pellets. In this machine, if it operates, it can experience excessive vibration and the force acting on the machine is close to its natural frequency and can cause damage, so it needs to be reduced. In this study, the objective of this research is to model and simulate vibrations in the gearbox and grinder to determine the results of the displacement and acceleration vibration responses on the pellet machine. In this study, an electric motor is used as a source of rotation and an input clutch as a connection between the shaft of the electric motor and the gearbox as a transmission to reduce the speed of the electric motor, where the rotation produced by the electric motor contains vibrations, the output coupling is the connecting shaft between the gearbox shaft and the shaft grinder and miller as a tool used to print pellets. From the existing physical form, mathematical equations and simulation blocks are constructed. In this research, it is found that the vibration response generated from the gearbox and grinder can be modeled with the x and z axes as the center of the system. The higher the vibration response, the higher the given frequency, the greater the amplitude and rms of the displacement and acceleration responses in each part, namely the motor, clutch in, gearbox gearbox, coupling out, and grinder will be greater. The result of displacement vibration response yields an rms of 1.956. The worm gear in the gearbox produces a displacement vibration of 1.0585 m and an acceleration of 6.8485 m/s2. The mill produces a displacement vibration of 1.0891 m and an acceleration of 5.1095 m/s2.